Characteristics of hellp syndrome in severe preeclampsia patients in dr. Soetomo hospital surabaya - P, Warih Angesti; Ernawati, Ernawati; Susanti, Dwi (Folia Medica Indonesiana, 2016)
Hemolysis, elevated liver enzyme, and low platelet count syndrome (HELLPs) is complication following severe preeclampsia which is one of the three leading causes of maternal mortality in Indonesia. The purpose of this study was to understand the prevalence, characteristics, and post-partum outcome of HELLPs patients who deliver in Dr. Soetomo Hospital in July 2012-June 2013. This study was observational-descriptive, cross sectional study. The population observed was the severe preeclampsia patients who deliver in Dr. Soetomo Hospital and have complete medical data in July 2012-June 2013. study subject taken by total sampling. HELLPs follow the 7% of severe preeclampsia patients. The maternal average age of HELLPs group was 30.2 (19-43), while in non-HELLPs was 30.8 (17-46). Most HELLPs patients were in the first and second pregnancy. The average of gestational age at labor in HELLPs was 33-34 weeks. Both in HELLPs and non-HELLPs most performed Cesarean Section delivery. No post-partum maternal mortality found in HELLPs, but 25% had stillbirth. The average of birth weight in HELLPs was 1994.4 g. First minute Apgar score >7 was 33.3% in HELLPs group. In conclusion, Most HELLPs patients were in the first and second pregnancy, while non-HELLPs were in first pregnancy. The average of gestational age at labor was lower in HELLPs group. Neonates mortality were higher in HELLPs group. The average of birth weight was lower in HELLPs group. First minute Apgar score > 7 was higher in non-HELLP group.